Kajian Keterampilan Membaca di Sekolah Dasar (Analisis Bibliometrik dari Tahun 2016-2020) - Tanzila, Dinda Lutfina; Sunarya, Dede Tatang; Julia, J. (Jurnal Pena Ilmiah, 2021)
This research aimed to mapp and analyze the topic that published in reputable international journals during 2016-2020 based on the Scopus database. There were four stages to collect the data includes; found bibliographies by using Publish or Perish (PoP) software, filtered out the articles, checked and completed metada in EndNote X9, and then analyzed the bibliographies using VOSViewer. The results showed that: 1) the number of citations realatively low but the trend of publications started to increase and reflectedÂ  the researchers interest in conducting a research about reading skill in elementary school. 2) the authors collaboration analysis showed that there were not occur widely collaboration. 3) the highest number ofÂ  the trend of title terms is â€œskillâ€. 4) the highest number ofÂ  the trend of title terms is â€œreading comprehensionâ€. 5) the highest number of trend of abstract terms is â€œstudentâ€™â€™. The reasearch concluded that publications of reading skills in elementary school articles have increased, but authors collaboration and the number of citations relatively low. The authors collaboration was an opportunity to further the research.